Accelerated Tau Aggregation, Apoptosis and Neurological Dysfunction Caused by Chronic Oral Administration of Aluminum in a Mouse Model of Tauopathies. (3rd May 2013) - Oshima, Etsuko; Ishihara, Takeshi; Yokota, Osamu; Nakashima‐Yasuda, Hanae; Nagao, Shigeto; Ikeda, Chikako; Naohara, Jun; Terada, Seishi; Uchitomi, Yosuke
Abstract To clarify whether long‐term oral ingestion of aluminum (Al) can increase tau aggregation in mammals, we examined the effects of oral Al administration on tau accumulation, apoptosis in the central nervous system (CNS) and motor function using tau transgenic (Tg) mice that show very slowly progressive tau accumulation. Al‐treated tau Tg mice had almost twice as many tau‐positive inclusions in the spinal cord as tau Tg mice without Al treatment at 12 months of age, a difference that reached statistical significance, and the development of pretangle‐like tau aggregates in the brain was also significantly advanced from 9 months. Al exposure did not induce any tau pathology in wild‐type (WT) mice. Apoptosis was observed in the hippocampus in Al‐treated tau Tg mice, but was virtually absent in the other experimental groups. Motor function as assessed by the tail suspension test was most severely impaired in Al‐treated tau Tg mice. Given our results, chronic oral ingestion of Al may more strongly promote tau aggregation, apoptosis and neurological dysfunction if individuals already had a pathological process causing tau aggregation. These findings may also implicate chronic Al neurotoxicity in humans, who frequently have had mild tau pathology from a young age.